Perceptions of Retired Nurses on Factors Preventing Younger Professional Nurses from Applying the Ethos of Ubuntu in Professional Care - Fhumulani M. Mulaudzi PhD; Rafiat Ajoke Anokwuru PhD; Ramadimetja Mogale PhD; Seepaneng Salaminah Moloko-Phiri PhD; Moselene AR DuPlessis PhD (SAGE Publishing, 2022)
Introduction Younger professional nurses are the future of the nursing profession and they receive the baton from older and retired nurses to continue the profession in good light. Ubuntu is an African philosophy that is embedded in caring ethics and it is viewed as a core value of the nursing profession and is highly valued by older nurses. Objective We explored the perceptions of retired nurses on factors that prevent younger professional nurses from applying the ethos of Ubuntu in professional care. Methods In this study, we explored the factors that prevent younger professional nurses from applying the ethos of Ubuntu in professional care. In this qualitative explorative study, data were collected during focus group discussions in a workshop held with 40 retired nurses in a province in South Africa. The transcripts were analyzed following the six steps outlined by Braun and Clarke (2006). Results Based on the perceptions of the retired nurses two main themes emerged as factors that prevent the younger professional nurses from applying the ethos of Ubuntu in their professional practice; 1) Motivation to practice Ubuntu in nursing, 2) Lack of political will to recognize nursing. Conclusion Retired nurses felt that Ubuntu could be applied in nursing care if these factors are addressed by both nurses and stakeholders.